2010
DOI: 10.1002/pbc.22605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of daily medication adherence among children with sickle cell disease: A 1‐year retrospective cohort analysis

Abstract: The objective of this study is to determine the prevalence of adherence to daily medications among children with sickle cell disease (SCD). Prescription records for 12 months were obtained from participants who had insurance in a Medicaid-based single health maintenance organization. Adherence was measured as a ratio between the number of expected days and the observed days between two refill periods for daily medications. A total of 93 children were studied. The average refill prescription rate was 58.4%. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 17 publications
0
50
0
5
Order By: Relevance
“…In a study of Medicaid-insured children from 2 states, Cox et al found that only 41% of days were covered with an antibiotic prescription, and only 22% of children had 75% or more days covered in a year, 15 slightly lower than our measured adherence. In other Medicaid-insured populations of children with SCD, Patel et al found 55% coverage for antibiotics, which was similar to the compliance observed in the same population for other medications (range: 59–61%), 16 and Beverung et al observed a mean of 45% of days covered with antibiotics, with fewer than 1 in 5 children meeting their full adherence threshold of 80%. 17 …”
Section: Discussionmentioning
confidence: 52%
“…In a study of Medicaid-insured children from 2 states, Cox et al found that only 41% of days were covered with an antibiotic prescription, and only 22% of children had 75% or more days covered in a year, 15 slightly lower than our measured adherence. In other Medicaid-insured populations of children with SCD, Patel et al found 55% coverage for antibiotics, which was similar to the compliance observed in the same population for other medications (range: 59–61%), 16 and Beverung et al observed a mean of 45% of days covered with antibiotics, with fewer than 1 in 5 children meeting their full adherence threshold of 80%. 17 …”
Section: Discussionmentioning
confidence: 52%
“…In spite of the known benefit, the penicillin adherence rates in most studies were less than 80 % [14][15][16][17][18][19]. Our personal experiences regarding HU in the clinic indicated a similarly low figure.…”
Section: Discussionmentioning
confidence: 89%
“…Only 1 article compared adherence to different types of medications for SCD and found similar rates of adherence for hydroxyurea (mean MPR 60%), folic acid (mean MPR 61%), and penicillin (mean MPR 55%). 28 …”
Section: Adherence Ratesmentioning
confidence: 99%